3D magnetic buoyancy-driven flow of hybrid nanofluids confined wavy cubic enclosures including multi-layers and heated obstacle. (July 2021) - Bendrer, B.A.I; Abderrahmane, Aissa; Ahmed, Sameh E.; Raizah, Zehba A.S.
Abstract: This paper provides numerical simulations of the magnetic convective process based on buoyancy forces within three dimensional wavy cubic enclosures. The flow domain is partitioned into two layers specifically, a porous layer and a hybrid nanofluid layer. The upper and lower plans of the domain are adiabatic while the residual plans are mentioned to relatively low temperatures. The temperature disparity within the flow domain is a result of a rectangular heated area that is located in the bottom plane. The magnetic force is taken in the normal direction ( Z -direction). As for the porous matrix, the Brinkman-extended non-Darcy model was chosen to simulate its effects. The method of solution is based on the Galerkin finite element, the outcomes are represented using various illustrations and tools. It is noticeable that changing the location of the heated area is a beneficial factor for this convective situation. Also, when Ha is altered from 0 to 100, a drop in values of the stream function is given up to 84.78%.